Gagalnya Pemahaman Fir'aun (X) dalam Perspektif Kajian Sain Alamtologi Pada Menerima Pesan Komunikasi - Marzuki (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
This research explains the failure of fir un in communication is the result of failing to understand one's own communication and when it fails to communicate with itself, fir un has lost its power and as a result of Fir un's arrogance and wants to monopolize power and want his greatness to last, finally the destruction felt by Fir un. and he considers himself a god because he wants to dominate and treat other people, including those beside him. Until finally fir`un fell from power because fir un lost the trust of his own people. Fir`un failed to communicate with the environment until fir un carried out a massacre in his own community and people and was afraid of a replacement. And if they do not communicate and deliberate properly and have extraordinary ambitions, then fir un eventually lost power, because they had persecuted their own people because they were too confident in power and played with extraordinary attitudes, then fir un's power was destroyed. Self-destruction at fir un is indirectly doing self-destruction, So good communication is being able to bring power to a more advanced and dignified direction. Poor communication can be fatal and devastating. So the conclusion in this scientific work is that the basis of the study of naturaltology is that the failure of fir un in receiving messages and communication has caused its own destruction.